Afrobeat! Fela and the Imagined Continent Revised Edition - Olorunyomi, Sola (Africae Monographs, 2022)
In the seventies, as signs of decay began to show in the capitalist experiment of the newly independent African countries, a "bard of the misrule" emerged on the streets of Lagos. Often shirtless and armed with his trademark saxophone, Fela Anikulapo Kuti tore his way into popular culture with Afrobeat music. Blending ethno-traditional forms with the reigning highlife and jazz rhythms, Afrobeat drew lyrics from the flip side of neo-colonial society and Fela's London and American experience in the sixties. In the two decades that followed, Fela ruled the nights from Afrika Shrine, his signature night club, and the days from the turntables of the restless city dwellers along the Atlantic coastline. Fela's Afrobeat became a dynamic mode of expression in the social history of post-independent West Africa and generated a counterculture that bonded through music, drugs, resistance politics-and ultimately, the nascence of an Afrocentric contemporary global culture.